Occupational exposures and mortality from cardiovascular disease among women textile workers in Shanghai, China. (19th October 2011) - Gallagher, Lisa G; Ray, Roberta M; Li, Wenjin; Psaty, Bruce M; Li Gao, Dao; Thomas, David B; Checkoway, Harvey
Abstract : Objectives: To explore whether cardiovascular disease (CVD) mortality is associated with occupational exposures in the textile industry, including bacterial endotoxin, a contaminant in cotton dust and a potent inflammagen. Methods: A cohort of 267 400 female textile workers in Shanghai, China was followed for CVD mortality from 1989 to 2000. Exposures at the factories were approximated by 10 sector classifications based on materials manufactured. We calculated age-standardised mortality by sector for ischemic heart disease, ischemic stroke, and haemorrhagic stroke. We used Cox proportional hazard modeling to calculate hazard ratios (HRs) and 95% CIs, adjusting for age and smoking, to compare the cotton spinning, weaving and knitting (SWK) sector to the remainder of the cohort (eg, silk SWK, synthetic SWK). Quantitative endotoxin exposure measures were available for a subset of the cohort (n=2895), and used to similarly calculate HRs. Results: Age-standardised mortality for hemorrhagic stroke were greater for the cotton SWK sector (30.5 per 100 000 person-years) compared to most other sectors (11.3–27.7). Cotton sector workers had slightly elevated mortality risk from hemorrhagic stroke (HR=1.19, 95% CI 1.08 to 1.31) or ischemic stroke (HR=1.15, 95% CI 0.99 to 1.34), but not ischemic heart disease (HR=1.05, 95% CI 0.88 to 1.26). We did not observe a strong relationship between stroke mortality and endotoxin exposure (based on 60 stroke deaths). Ischemic heart disease mortality outcomes were too infrequent in the cohort subset for analysis. Conclusions: Exposures in cotton textile factories may contribute to stroke mortality among women, but further research is warranted to identify specific exposures that might underlie this relationship.